Effect of a Combined Strengthening and Proprioceptive Training Program on Balance and Gait of Female Children With Intellectual Disability - Mohammad javad Azimizadeh; Seyyed Hosein Hoseini; Ali Asghar Norasteh (Biyumikānīk-i varzishī)
Objective: This study aims to assess the effect of combined strengthening and proprioceptive exercises on balance and gait of female children with intellectual disability Methods: Participants were 24 elementary school girls aged 9-13 years in Mashhad, Iran who were selected using a convenience sampling method and divided to two groups of exercise and control. The exercise group performed selective exercises for 8 weeks, while the control group performed their daily activities. In the pre-test stage, the static balance, dynamic balance, lower limb strength, and gait were measured. After eight weeks, all variables were measured again. Results: Eight weeks of strengthening and proprioceptive exercises had a significant effect on improvement of static balance, dynamic balance, lower limb strength, and gait of girls with intellectual disability (P=0.001). Conclusion: Eight weeks of strengthening and proprioceptive exercises can be used to improve the physical fitness factors of girls with intellectual disability.